The positivity rates and drug resistance patterns of Mycobacterium tuberculosis using nucleotide MALDI-TOF MS assay among suspected tuberculosis patients in Shandong, China: a multi-center prospective study - Gao, Xusheng; Li, Tongxia; Han, Wenge; Xiong, Yu; Xu, Shiyang; Ma, Hongbao; Wang, Qing; Zhang, Qiuxia; Yang, Guofeng; Xie, Dan; Jiang, Peipei; Wu, Hailiang; et al. (Frontiers in Public Health, 2024)
Objective To investigate the positivity rates and drug resistance characteristics of Mycobacterium tuberculosis (MTB) among suspected tuberculosis (TB) patients in Shandong Province, the second-largest population province in China. Methods A prospective, multi-center study was conducted from April 2022 to June 2023. Pathogen and drug resistance were identified using nucleotide matrix-assisted laser desorption ionization time-of-flight mass spectrometry (nucleotide MALDI-TOF MS). Results Of 940 suspected TB patients included in this study, 552 cases were found to be infected with MTB giving an overall positivity rate of 58.72%. Total of 346 cases were resistant to arbitrary anti-TB drug (62.68%), with Zibo (76.47%), Liaocheng and Weihai (both 69.23%) ranking top three and TB treatment history might be a related factor. Monoresistance was the most common pattern (33.53%), with isoniazid the highest at 12.43%, followed by rifampicin at 9.54%. Further analysis of gene mutations conferring resistance revealed diverse types with high heteroresistance rate found in multiple anti-TB drugs. Conclusion A relatively high rate of MTB positivity and drug resistance was found in Shandong Province during and after the COVID-19 pandemic, indicating the need for strengthening rapid identification of species and drug resistance among suspected TB patients to guide better medication and minimize the occurrence of drug resistance.